Dinamics of Group B Streptococcus and Enterococcus faecalis associated with genital tract infections of dairy cows from two farms of county Iași - Alexandra Andreea Sikra; Cristina Mihaela Rimbu; Cristina Horhogea; Stefan Gregore Ciornei; Petru Rosca; Dan Gheorghe Drugociu (Cluj Veterinary Journal, 2021)
Abstract: The involution of the postpartum bovine uterus is accompanied by bacterial invasion. Studies show that most, if not all, bovine uteri are bacterially contaminated in the immediate postpartum period. The culture at this time will usually produce a wide range of bacteria, including Actinomyces pyogenes, Streptococcus spp., Staphylococcus spp. and Clostridium spp., Coliforms and Gram-negative anaerobes.